Case Report: SARS-CoV-2 Mother-to-Child Transmission and Fetal Death Associated With Severe Placental Thromboembolism - Marinho, Penélope Saldanha; da Cunha, Antonio José Ledo Alves; Chimelli, Leila; Avvad-Portari, Elyzabeth; Andreiuolo, Felipe da Matta; de Oliveira-Szejnfeld, Patrícia Soares; Mendes, Mayara Abud; Gomes, Ismael Carlos; Souza, Letícia Rocha Q.; Guimarães, Marilia Zaluar; Goldman, Suzan Menasce; de Oliveira, Mariana Barros Genuíno; et al. (Frontiers in Medicine, 2021)
SARS-CoV-2 infection during pregnancy is not usually associated with significant adverse effects. In this study, however, we report a fetal death associated with mild Covid-19 in a 34-week pregnant woman. The virus was detected in the placenta (15 times more on the fetal side) and in an unprecedent way in several fetal tissues. Placental abnormalities (MRI and anatomopathological study) were consistent with intense vascular malperfusion, probably the cause of fetal death. Lung histopathology also showed signs of inflammation, which could have been a contributory factor. Monitoring inflammatory response and coagulation in high-risk pregnant women with Covid-19 may prevent unfavorable outcomes, as shown in this case.